ANALISIS PENGARUH FUNDAMENTAL TERHADAP PERGERAKAN NILAI TUKAR RUPIAH TERHADAP DOLLAR AMERIKA - Renny Mointi (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
The purpose of this research is to know the fundamental influence of inflation on rupiah exchange rate against US dollar or USD / IDR, Bank Indonesia interest rate against rupiah exchange rate against US dollar (USD / IDR), gross domestic product against the movement of the rupiah against the US dollar / USD / IDR. The analytical method used to know Influence of Inflation, Interest Rate to US dollar (USD / IDR), is by using multiple linear regression analysis. SPSS program version 17.0. The result of the research shows that inflation has a positive and significant effect on the movement of the rupiah against the US dollar (USD / IDR). The interest rates of Bank Indomesia affect the movement of exchange rate of American products and gross domestic product have positive and insignificant effect to US dollar (USD / IDR)